Biodegradation of plastics in soil: The effect of temperature - Pischedda, Alessandro; Tosin, Maurizio; Degli-Innocenti, Francesco (Polymer degradation and stability, 2019)
The assessment of the intrinsic biodegradability of plastic materials is made under optimized environmental conditions in order not to limit the microbial growth and activity and follow the biodegradation process until completion. In particular, biodegradation tests are carried out at constant temperature in the range between 20 and 28 °C in order to favour the growth of mesophilic microorganisms. On the other hand, if the purpose is to predict the environmental fate of consumer or professional products made with biodegradable plastics after accidental or deliberate release into the environment, then the biodegradation rate attainable under less optimal conditions should be estimated. In this work pellets of a commercial biodegradable plastic material were tested for soil biodegradation at 28, 20, and 15 °C. The CO2 evolution was followed for more than one year using the ASTM D 5988–18 test method. The mineralization rates (mg C/day, i.e. the amount of organic carbon converted into CO2 per day) were determined by applying a linear regression from day 140 onwards on the organic carbon depletion curves, when the biodegradation reaction was constant. The specific mineralization rates, i.e. the rate per surface area unit (mg C/day/cm2) were determined by dividing the mineralization rates by the available surface areas of the pellets tested. A thermal performance curve (TPC) was obtained by plotting the specific mineralization rates against the respective temperatures. The TPC curve was perfectly described by an exponential model that was in agreement with the Arrhenius equation. This suggests that biodegradation is dominated by simple thermodynamic effects in the tested temperature ranges (15–28 °C). The apparent activation energy of the biodegradation reaction was 108.7 kJ/mol. Using the TPC, it was possible to estimate the time needed for total mineralization of a product made with the test material with a given surface area when exposed to different temperatures. Clearly, the effective biodegradation rate was affected by other environmental factors (e.g. nutrients, pH, gas exchange, etc.) besides temperature. The current work indicates that temperature, an important environmental factor, affects biodegradation rates, in accordance with the Arrhenius equation. The observation that the apparent activation energy of the biodegradation reaction does not vary with temperature in the tested temperature range indicates a persistency in the metabolic activities of the involved mesophilic microbial communities. •Biodegradation in soil is affected by the testing temperature.•The rates and temperatures are perfectly described by the Arrhenius equation.•This suggests that biodegradation is dominated by simple thermodynamic effects.•This is important information for environmental fate studies.